The Massachusetts School-Based Body Mass Index Experiment—Gleaning Implementation Lessons for Future Childhood Obesity Reduction Efforts - Stanford, Fatima Cody (Obesity (Silver Spring), 2014)
In 2009, Massachusetts (MA) Department of Public Health (DPH) implemented new regulations that required public schools in the state to measure height and weight, determine body mass index (BMI), and notify parents of children in grades 1, 4, 7, and 10 of their child’s weight status. After 3 years of implementation, MA DPH recently abandoned parental notification of school-based BMI screening results citing several concerns including flaws in the ability to monitor the way that the BMI screening results were communicated from the schools to parents/guardians and some reports of breaches in confidentiality of students’ measurements. In this article, we review implementation issues that could have impacted the success of the MA DPH regulation as well as lessons to be learned and potentially applied to future childhood obesity efforts.